Grain-oriented electrical steel sheet, method for producing grain-oriented electrical steel sheet, and method for evaluating grain-oriented electrical steel sheet
By forming a coating of specific components on both surfaces of the oriented electromagnetic steel plate and baking, the problem of insufficient insulation in the transformer core is solved, and the effect of excellent insulation and reduced iron loss is achieved.
Patent Information
- Application Number
- CN202180068568.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-10-21
- Filing Date
- 2021-07-26
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2041-07-26
AI Technical Summary
When the orientation electromagnetic steel plate is processed into the core of the transformer, the insulation may become insufficient, resulting in leakage current and partial discharge.
By forming a coating of specific components on both surfaces of the steel plate and baking at high temperatures to form a coating, combining specific molar ratios and treatment conditions, the hardness and surface roughness of the coating are ensured within a suitable range.
It achieves excellent insulation when the transformer core is used, avoids the problems of leakage current and local discharge, and reduces iron loss.
Smart Images

Figure BDA0004163892860000061 
Figure BDA0004163892860000211 
Figure BDA0004163892860000251
Abstract
Description
Technical Field
[0001] The present invention relates to a grain-oriented electrical steel sheet, a method for producing the grain-oriented electrical steel sheet, and a method for evaluating the grain-oriented electrical steel sheet. Background Art
[0002] Generally, a coating is formed on both surfaces of a grain-oriented electrical steel sheet to impart insulation properties, etc. Such a coating includes, for example, a so-called insulating coating formed on a forsterite coating formed during final annealing in the production process of the grain-oriented electrical steel sheet.
[0003] Patent Documents 1 and 2 each disclose an insulating coating formed by baking a coating liquid containing phosphate, colloidal silica, and chromic anhydride.
[0004] Such an insulating film has a low thermal expansion coefficient. Therefore, when it is formed at a high temperature and then cooled, the difference in thermal expansion coefficient with the steel sheet causes tension to be applied to the steel sheet, thereby reducing iron loss.
[0005] Prior art literature
[0006] Patent Literature
[0007] Patent Document 1: Japanese Patent Publication No. 56-52117
[0008] Patent Document 2: Japanese Patent Publication No. 53-28375 Summary of the invention
[0009] Problems to be solved by the invention
[0010] The grain-oriented electrical steel sheets are stacked and used as, for example, an iron core of a transformer.
[0011] When grain-oriented electromagnetic steel sheets having insufficient insulation properties (interlaminar resistance) are stacked and used as a transformer core, leakage current and partial discharge may occur.
[0012] Even if the insulation of a grain-oriented electrical steel sheet is at a level that is acceptable in an inspection before product shipment, it may be insufficient when processed into a transformer core. Therefore, a grain-oriented electrical steel sheet that exhibits good insulation even when processed into a transformer core is desired.
[0013] The present invention has been made in view of the above viewpoints, and an object of the present invention is to provide a grain-oriented electrical steel sheet having excellent insulating properties.
[0014] Methods used to solve problems
[0015] The present inventors have conducted intensive studies and, as a result, have found that the above-mentioned object can be achieved by adopting the following configuration, thereby completing the present invention.
[0016] That is, the present invention provides the following [1] to [7].
[0017] [1] A grain-oriented electrical steel sheet comprising a steel sheet and a coating disposed on both surfaces of the steel sheet, wherein the interlayer current value after a friction test is 0.10 A or less. The friction test is performed by stacking two grain-oriented electrical steel sheets and reciprocating 90 times under the conditions of a surface pressure of 200 Pa, a friction speed of 0.10 m / s, and a reciprocating stroke of 50 mm.
[0018] [2] The grain-oriented electrical steel sheet according to [1] above, wherein the hardness of the coating is 9.0 GPa or less.
[0019] [3] The grain-oriented electrical steel sheet according to [1] or [2], wherein the surface roughness of the coating is 6.0 μm or less in terms of maximum peak height Sp.
[0020] [4] The grain-oriented electrical steel sheet according to any one of [1] to [3] above, wherein the steel sheet has a steel composition containing, in mass %, 2.0 to 4.0% Si and 0.03 to 0.25% Mn, with the balance being Fe and inevitable impurities.
[0021] [5] The grain-oriented electrical steel sheet according to [4], wherein the steel composition further contains, in terms of mass %, at least one selected from the group consisting of Ni: 1.50% or less, Cr: 0.50% or less, Cu: 0.50% or less, P: 0.100% or less, Sb: 0.500% or less, Sn: 0.500% or less, Bi: 0.100% or less, Mo: 0.100% or less, Nb: 0.0100% or less, V: 0.010% or less, Ti: 0.010% or less, and Ta: 0.010% or less.
[0022] [6] A method for manufacturing a grain-oriented electrical steel sheet, comprising applying a coating liquid to a conveyed steel sheet, baking at a temperature of 700° C. or higher, and cooling the steel sheet to form a coating on both surfaces of the steel sheet, wherein the steel sheet is cooled to a forward slip ratio r of 1.7% or less in a conveying region where the steel sheet is cooled to 600° C. or less, and wherein the coating liquid comprises a molar ratio M1 / S of a metal element M1 content to a silicon dioxide S content calculated as SiO2 of 0.15 or more, a molar ratio M2 / S of a metal element M2 content to a silicon dioxide S content calculated as SiO2 of 0.15 or less, and a molar ratio P / S of a phosphoric acid component P content calculated as P2O5 to a silicon dioxide S content calculated as SiO2 of 0.20 or more, wherein the metal element M1 is at least one selected from the group consisting of Zn, Li, Mg, and Ca, and the metal element M2 is at least one selected from the group consisting of Zr, Ti, Cr, and Al.
[0023] [7] A method for evaluating a grain-oriented electromagnetic steel sheet, the method comprising: performing a friction test, obtaining an interlayer current value of the grain-oriented electromagnetic steel sheet after the friction test, and determining the insulation quality of the grain-oriented electromagnetic steel sheet based on the obtained interlayer current value. The friction test is performed by overlapping two grain-oriented electromagnetic steel sheets and reciprocating 60 to 120 times under the conditions of a surface pressure of 150 to 250 Pa, a friction speed of 0.05 to 0.15 m / s, and a reciprocating stroke of 30 to 70 mm.
[0024] Effects of the Invention
[0025] According to the present invention, a grain-oriented electrical steel sheet having excellent insulating properties can be provided. DETAILED DESCRIPTION
[0026] [Consideration of the present inventors (Evaluation method of grain-oriented electrical steel sheet)]
[0027] First, the present inventors prepared a plurality of types of grain-oriented electrical steel sheets (including “grain-oriented electrical steel sheets of the present invention” described later) produced by various methods as test sheets.
[0028] In general, a grain-oriented electrical steel sheet includes a steel sheet and a coating (insulating coating) disposed on both surface sides of the steel sheet, and the hardness and surface roughness of the coating differ depending on the test sheet.
[0029] Next, each test plate was cut at an angled cutting line and then stacked to form an iron core to manufacture a transformer, and electricity was supplied to the manufactured transformer.
[0030] As a result, a transformer in which leakage current and partial discharge occurred was confirmed. In other words, a test plate in which insulation (interlayer resistance) was insufficient when processed into a transformer core was confirmed.
[0031] For each test plate, the surface insulation resistance was measured according to the A method described in JIS C 2550-4:2019 before the transformer was manufactured, and the resistance value was 200 Ω·cm. 2 In the above, no abnormality was observed in the insulation properties (interlayer resistance).
[0032] Therefore, the inventors of the present invention believe that the interlayer resistance may deteriorate during the process of manufacturing the transformer. Specifically, it is believed that during the process of processing the test plates into the iron core of the transformer, the test plates rub against each other, and at this time, the surface of the test plates is scratched and the coating is partially peeled off, resulting in the deterioration of the interlayer resistance.
[0033] Such defects are not easy to occur in the normal transformer manufacturing process. However, for some reasons, the oriented electromagnetic steel sheets are sometimes processed into the transformer core under severe conditions such as rubbing against each other with high surface pressure for many times. In this case, the above defects are easy to occur.
[0034] Therefore, the present inventors conducted a test (friction test) in which test plates of the same grain-oriented electrical steel sheet were repeatedly rubbed against each other under various conditions and then measured the surface insulation resistance. As a result, the resistance value of the test plates sometimes decreased, that is, the insulation (interlayer resistance) sometimes became insufficient.
[0035] The present inventors have conducted further studies and found that the insulation properties of a grain-oriented electrical steel sheet (insulation properties when the grain-oriented electrical steel sheet is processed into a transformer core) can be determined based on the interlaminar current value of the grain-oriented electrical steel sheet after a specific friction test.
[0036] Here, the "interlayer current value" is defined as follows.
[0037] That is, in the A method described in JIS C 2550-4:2019, the average value of the current flowing through all the contact electrodes is set to I A , when the total area of all contact electrodes is set to A, the interlayer resistance R A Using the formula R A =A(1 / I A -1) indicates that the I A Defined as "interlayer current value".
[0038] Interlayer resistance R A By the current value I A Therefore, even if the current changes slightly, the interlayer resistance R ATherefore, the interlayer current value (current value I A ) to appropriately evaluate the insulation properties (interlayer resistance R A )’s subtle differences.
[0039] In the study, specifically, the present inventors first prepared good materials and bad materials as test plates of grain-oriented electromagnetic steel sheets to be processed into the iron core of a transformer.
[0040] The surface insulation resistance (resistance value) of both good and bad materials measured by method A of JIS C2550-4:2019 before being processed into transformer cores was 200Ω·cm 2 In the above, no abnormality was confirmed in the insulation properties (interlayer resistance).
[0041] However, a transformer manufactured using a good material for the core does not generate leakage current or partial discharge and has good insulation. On the other hand, a transformer manufactured using a poor material for the core generates leakage current and partial discharge and has insufficient insulation.
[0042] For good materials and bad materials, friction tests were conducted under the conditions (surface pressure, friction speed, reciprocating stroke, and number of reciprocating strokes) shown in Table 1 below. Ten friction tests were conducted under each condition, and then the interlayer current value (unit: A) was obtained. For the interlayer current value obtained, the average (μ) and standard deviation (σ) of 10 times are shown in Table 1 below.
[0043] [Table 1]
[0044] Table 1
[0045]
[0046] Regarding the above Table 1, first, the interlayer current values of No. 1 to 5 which differ only in surface pressure (other conditions are constant) are referred to.
[0047] Among them, in the case of No. 2 (surface pressure: 150Pa), the μ+σ value (0.04) of the good material did not reach the μ-σ value (0.07) of the bad material, and the interlayer current values of the good material and the bad material were obviously different. In this case, "○" is recorded in the pass / fail column of the above Table 1. The same is true for No. 3 to 4.
[0048] In contrast, in the case of No. 1 (surface pressure: 100 Pa), the μ+σ value (0.03) of the good material reached the μ-σ value (0.02) of the bad material, and the interlayer current values of the good material and the bad material could not be said to be significantly different. In this case, "×" is recorded in the pass / fail column of the above Table 1. The same is true for No. 5.
[0049] Similarly, "○" or "×" is recorded in the pass / fail column of Table 1 for Nos. 6 to 10 that differ only in friction speed, Nos. 11 to 15 that differ only in reciprocating stroke, and Nos. 16 to 20 that differ only in the number of reciprocating times.
[0050] From the results shown in Table 1, it is understood that when the friction test is performed under specific conditions, the quality of the insulation can be appropriately determined from the interlayer current value.
[0051] Specifically, the friction test is performed by stacking two identical grain-oriented electrical steel sheets and reciprocating 60 to 120 times under the conditions of a surface pressure of 150 to 250 Pa, a friction speed of 0.05 to 0.15 m / s, and a reciprocating stroke of 30 to 70 mm.
[0052] The present inventors further conducted studies on friction tests.
[0053] As a result, it was found that for some grain-oriented electrical steel sheets, when the friction test was carried out under the conditions of surface pressure 200Pa, friction speed 0.10m / sec, reciprocating stroke 50mm, and reciprocating number 90 times, the insulation property was good when the interlayer current value after the friction test was 0.10A or less. Specifically, it was found that even if the grain-oriented electrical steel sheet was processed into the iron core of a transformer, leakage current and partial discharge would not occur in the transformer.
[0054] Before manufacturing a transformer using a grain-oriented electrical steel sheet, a friction test is performed on the grain-oriented electrical steel sheet. If a sufficiently low interlayer current value is obtained, the transformer can be manufactured without paying special attention.
[0055] [Oriented electrical steel sheet]
[0056] Next, the grain-oriented electrical steel sheet of the present invention will be described.
[0057] The present invention comprises a steel plate and a coating disposed on both surfaces of the steel plate, and the interlayer current value after the friction test is 0.10 A or less. The friction test is performed by overlapping two grain-oriented electrical steel plates and reciprocating 90 times under the conditions of a surface pressure of 200 Pa, a friction speed of 0.10 m / sec, and a reciprocating stroke of 50 mm.
[0058] As described above, even if the grain-oriented electrical steel sheet of the present invention is processed into an iron core of a transformer, leakage current and partial discharge do not occur in the transformer, and the insulation property is excellent.
[0059] From the perspective of achieving better insulation properties, the interlayer current value is preferably 0.08 A or less, more preferably 0.05 A or less, and even more preferably 0.03 A or less.
[0060] When interlayer current does not flow, insulation is excellent, and therefore the lower limit of the interlayer current value is not particularly limited.
[0061] <Lamination>
[0062] As the coating, for example, a so-called insulating coating formed using a coating liquid described below can be mentioned. In this case, the composition of the coating is in accordance with the composition of the coating liquid described below.
[0063] "hardness"
[0064] When the coating is too hard, hard powder is generated during the friction test. This powder acts as an abrasive and scratches the coating, and the interlayer current value tends to increase.
[0065] Therefore, the hardness of the coating is preferably 9.0 GPa or less, more preferably 8.5 GPa or less, further preferably 8.0 GPa or less, and particularly preferably 7.5 GPa or less. When the hardness of the coating is within this range, the interlayer current value after the friction test becomes further reduced, and the insulation (interlayer resistance) is more excellent.
[0066] On the other hand, the lower limit of the hardness of the coating is not particularly limited, but is, for example, 5.0 GPa or more.
[0067] However, if the coating is too soft, the tension applied by the coating to the steel sheet may decrease, and the iron loss may increase. Therefore, from the viewpoint of reducing the iron loss, the hardness of the coating is preferably 6.0 GPa or more, and more preferably 6.5 GPa or more.
[0068] The hardness of the coating was determined by a nanoindentation method using a diamond triangular pyramid indenter (Berkovich type, apex angle: 60°).
[0069] Nanoindentation is a method in which the load and depth are continuously measured by pressing the indenter into the material, and the complex elastic modulus is obtained from the relationship between the indentation depth and the load.
[0070] More specifically, the coating of the grain-oriented electrical steel sheet was tested by pressing the indenter under the conditions of a loading time of 5 seconds, an unloading time of 2 seconds, and a maximum load of 1000 μN at room temperature using a linear load application method. The average of the values measured at any three locations was taken as the hardness of the coating.
[0071] Surface roughness
[0072] If the surface of the coating is excessively rough, the opposing coatings may be scratched during a friction test, and the interlayer current value may easily increase.
[0073] Therefore, the surface roughness of the coating is preferably 6.0 μm or less, more preferably 5.8 μm or less, and further preferably 5.5 μm or less in terms of maximum peak height Sp. When the maximum peak height Sp of the coating is within this range, the interlayer current value after the friction test becomes further reduced, and the insulation (interlayer resistance) is further improved.
[0074] The lower limit of the maximum peak height Sp of the coating is not particularly limited. However, if the maximum peak height Sp of the coating is too small, it may be difficult to stack the grain-oriented electrical steel sheets when processing them into transformer cores. Therefore, the maximum peak height Sp of the coating is preferably 1.0 μm or more.
[0075] The maximum peak height Sp of the coating is the average value of the values measured at any three positions using a three-dimensional roughness meter (SURFCOM 1500SD2-2 manufactured by Tokyo Seimitsu Co., Ltd., roughness stylus: tip R, 2 μm (60° conical diamond), measurement speed: 0.6 mm / sec, measurement area: 10 mm×10 mm) based on ISO 25178.
[0076] <Steel Plate>
[0077] Examples of the steel sheet include a steel sheet (grain-oriented electromagnetic steel sheet) after final annealing produced as described below.
[0078] First, a steel raw material is hot rolled by a known method to obtain a hot rolled sheet. The obtained hot rolled sheet is subjected to one or more hot rolled sheet annealing and cold rolling to obtain a cold rolled sheet of the final sheet thickness. The obtained cold rolled sheet is subjected to a recrystallization annealing, and then an annealing separator is applied and a final annealing is performed. If necessary, the unreacted annealing separator is removed by water washing, mild pickling, etc.
[0079] When an annealing separator containing MgO is used, a coating containing forsterite (forsterite coating) is formed on the surface of the obtained steel sheet. In this case, the coating such as the above-mentioned insulating coating is arranged on the forsterite coating.
[0080] The forsterite coating may not be formed, or may be removed by pickling or the like after being formed. In this case, the above-mentioned insulating coating or the like is directly disposed on the surface of the steel plate. In order to ensure the adhesion of the insulating coating, a base coating such as a ceramic coating other than the forsterite coating may be provided under the insulating coating.
[0081] Steel Composition
[0082] The steel plate has a steel composition containing, by mass%, 2.0 to 4.0% Si and 0.03 to 0.25% Mn, with the balance being Fe and inevitable impurities.
[0083] Si is an element that increases the resistivity of steel and reduces iron loss. Therefore, the amount of Si is preferably 2.0 mass % or more, and more preferably 2.8 mass % or more.
[0084] On the other hand, when Si is too much, workability may be reduced and rolling may become difficult to manufacture. Therefore, the amount of Si is preferably 4.0 mass % or less, and more preferably 3.7 mass % or less.
[0085] Mn is an element that improves the hot workability of steel. Therefore, the amount of Mn is preferably 0.03 mass % or more, and more preferably 0.04 mass % or more.
[0086] On the other hand, when the amount of Mn is too large, the magnetic flux density of the obtained grain-oriented electrical steel sheet may decrease. Therefore, the amount of Mn is preferably 0.25 mass % or less, and more preferably 0.20 mass % or less.
[0087] In order to improve the magnetic properties, the steel composition may further contain, in terms of mass %, at least one selected from the group consisting of Ni: less than 1.50%, Cr: less than 0.50%, Cu: less than 0.50%, P: less than 0.100%, Sb: less than 0.500%, Sn: less than 0.500%, Bi: less than 0.100%, Mo: less than 0.100%, Nb: less than 0.0100%, V: less than 0.010%, Ti: less than 0.010% and Ta: less than 0.010%.
[0088] When Ni is contained, in order to obtain the effect of addition, the Ni amount is preferably 0.01 mass % or more, more preferably 0.05 mass % or more. On the other hand, in this case, the Ni amount is 1.50 mass % or less, preferably 1.00 mass % or less, more preferably 0.50 mass % or less.
[0089] When Cr is contained, in order to obtain the effect of addition, the Cr amount is preferably 0.01 mass % or more, more preferably 0.03 mass % or more. On the other hand, in this case, the Cr amount is 0.50 mass % or less, preferably 0.35 mass % or less, more preferably 0.20 mass % or less.
[0090] When Cu is contained, in order to obtain the effect of addition, the amount of Cu is preferably 0.01 mass % or more, more preferably 0.02 mass % or more. On the other hand, in this case, the amount of Cu is 0.50 mass % or less, preferably 0.35 mass % or less, more preferably 0.20 mass % or less.
[0091] When P is contained, in order to obtain the effect of addition, the amount of P is preferably 0.005 mass% or more, more preferably 0.010 mass% or more. On the other hand, in this case, the amount of P is 0.100 mass% or less, preferably 0.080 mass% or less, more preferably 0.060 mass% or less.
[0092] When Sb is contained, in order to obtain the effect of addition, the Sb amount is preferably 0.005 mass % or more, more preferably 0.010 mass % or more. On the other hand, in this case, the Sb amount is 0.500 mass % or less, preferably 0.350 mass % or less, more preferably 0.200 mass % or less.
[0093] When Sn is contained, in order to obtain the effect of addition, the amount of Sn is preferably 0.005 mass % or more, more preferably 0.010 mass % or more. On the other hand, in this case, the amount of Sn is 0.500 mass % or less, preferably 0.350 mass % or less, more preferably 0.200 mass % or less.
[0094] When Bi is contained, in order to obtain the effect of addition, the Bi amount is preferably 0.001 mass % or more, more preferably 0.002 mass % or more. On the other hand, in this case, the Bi amount is 0.100 mass % or less, preferably 0.050 mass % or less, more preferably 0.010 mass % or less.
[0095] When Mo is contained, in order to obtain the effect of addition, the amount of Mo is preferably 0.005 mass % or more, more preferably 0.008 mass % or more. On the other hand, in this case, the amount of Mo is 0.100 mass % or less, preferably 0.085 mass % or less, more preferably 0.070 mass % or less.
[0096] When Nb is contained, in order to obtain the effect of addition, the amount of Nb is preferably 0.0010 mass % or more, more preferably 0.0020 mass % or more. On the other hand, in this case, the amount of Nb is 0.0100 mass % or less, preferably 0.0080 mass % or less, more preferably 0.0050 mass % or less.
[0097] When V is contained, in order to obtain the effect of addition, the amount of V is preferably 0.001 mass % or more, more preferably 0.002 mass % or more. On the other hand, in this case, the amount of V is 0.010 mass % or less, preferably 0.008 mass % or less.
[0098] When Ti is contained, in order to obtain the effect of addition, the amount of Ti is preferably 0.001 mass % or more, more preferably 0.002 mass % or more. On the other hand, in this case, the amount of Ti is 0.010 mass % or less, preferably 0.008 mass % or less.
[0099] When Ta is contained, in order to obtain the effect of addition, the amount of Ta is preferably 0.001 mass % or more, more preferably 0.002 mass % or more. On the other hand, in this case, the amount of Ta is 0.010 mass % or less, preferably 0.008 mass % or less.
[0100] [Method for producing grain-oriented electrical steel sheet]
[0101] Next, a method for producing the grain-oriented electrical steel sheet of the present invention (hereinafter, also referred to as "the production method of the present invention" for convenience) will be described.
[0102] In summary, the manufacturing method of the present invention is a method of forming a coating on both surfaces of the steel sheet while conveying the steel sheet using conveyor rollers.
[0103] In the manufacturing method of the present invention, the coating film is formed by applying the coating liquid to the conveyed steel sheet, baking at a temperature of 700° C. or higher, and cooling the steel sheet.
[0104] <Coating liquid>
[0105] First, components that may be contained in the coating liquid used in the production method of the present invention will be described.
[0106] 《Phosphoric acid component P and silicon dioxide S》
[0107] The coating liquid contains, for example, a phosphoric acid component P and silicon dioxide S.
[0108] Examples of the phosphoric acid component P include phosphoric acid and phosphates. Examples of the phosphate include phosphates containing metal elements such as the metal element M1 and the metal element M2 described below (metal phosphates), and dihydrogen phosphates are preferred from the viewpoint of availability.
[0109] Examples of the silica S include colloidal silica. The average particle size of the colloidal silica is not particularly limited, but is, for example, 1 to 100 nm, and preferably 5 to 50 nm.
[0110] Metal Element M1
[0111] The coating liquid contains, for example, at least one metal element M1 selected from the group consisting of Zn, Li, Mg, and Ca.
[0112] The metal element M1 can reduce the hardness of a coating formed using a coating liquid containing the metal element M1. When the coating contains an appropriate amount of the metal element M1, the interlayer current value after the friction test becomes small.
[0113] The metal element M1 is contained in the coating liquid as a metal species (cation) of a phosphate component P. Alternatively, the metal element M1 may be contained in the coating liquid in the form of various compounds such as oxides, hydroxides, sulfates, nitrates, and carbonates.
[0114] Metal Elements M2
[0115] The coating liquid contains, for example, at least one metal element M2 selected from the group consisting of Zr, Ti, Cr, and Al.
[0116] The metal element M2 can increase the Young's modulus of the coating formed using the coating liquid containing the metal element M2. As described above, the metal element M1 reduces the hardness of the coating, thereby reducing the tension applied to the steel sheet by the coating. In this case, the reduction in tension can be suppressed by using the metal element M2 in combination.
[0117] The metal element M2 is contained in the coating liquid in the form of a metal species (cation) of a phosphate component P. Alternatively, the metal element M2 may be contained in the coating liquid in the form of various compounds such as oxides, hydroxides, sulfates, nitrates, and carbonates.
[0118] Next, the content of each of the above components in the coating liquid will be described.
[0119] 《Molar ratio M1 / S》
[0120] As described above, the metal element M1 reduces the hardness of the coating.
[0121] In the coating liquid, the molar ratio M1 / S of the content of the metal element M1 to the content of the silicon dioxide S in terms of SiO2 is 0.15 or more. This prevents the formed coating from becoming excessively hard, and reduces the interlayer current value after the friction test.
[0122] From the viewpoint of achieving a more excellent effect, the molar ratio M1 / S is preferably 0.20 or more, and more preferably 0.25 or more.
[0123] On the other hand, the upper limit of the molar ratio M1 / S is not particularly limited, and is, for example, 0.40 or less.
[0124] However, from the viewpoint of reducing iron loss, the molar ratio M1 / S is preferably 0.35 or less, and more preferably 0.30 or less. When the molar ratio M1 / S is within this range, the coating liquid is stable, the coating property is excellent, and the coating can be uniformly formed. As a result, the tension is stably applied to the steel sheet, and the effect of reducing iron loss is excellent.
[0125] 《Molar ratio M2 / S》
[0126] In the coating liquid, the molar ratio M2 / S of the content of the metal element M2 to the content of the silicon dioxide S in terms of SiO2 is 0.15 or less. As a result, the surface of the formed coating is not excessively rough, and the interlayer current value after the friction test becomes small.
[0127] From the viewpoint of achieving a more excellent effect, the molar ratio M2 / S is preferably 0.10 or less, and more preferably 0.08 or less.
[0128] On the other hand, the lower limit of the molar ratio M2 / S is not particularly limited, and is, for example, 0.01 or more.
[0129] However, from the viewpoint of reducing iron loss, the molar ratio M2 / S is preferably 0.02 or more, and more preferably 0.05 or more. As described above, the metal element M2 can increase the Young's modulus of the coating. When the molar ratio M2 / S is within this range, the Young's modulus of the coating can be increased, thereby stably applying tension to the steel sheet, and the effect of reducing iron loss is excellent.
[0130] 《Molar ratio P / S》
[0131] In the coating liquid, the molar ratio P / S of the content of the phosphoric acid component P converted to P2O5 and the content of the silicon dioxide S converted to SiO2 is 0.20 or more. As a result, the formed film does not become excessively hard, and the interlayer current value after the friction test becomes small. In addition, the film forming property becomes good, the generation of cracks in the formed film can be suppressed, and the corrosion resistance is excellent.
[0132] From the viewpoint of achieving a more excellent effect, the molar ratio P / S is preferably 0.23 or more, and more preferably 0.25 or more.
[0133] On the other hand, the upper limit of the molar ratio P / S is not particularly limited, but is, for example, 0.50 or less.
[0134] However, from the viewpoint of reducing iron loss, the molar ratio P / S is preferably 0.40 or less, and more preferably 0.35 or less. When the molar ratio P / S is within this range, the formed film stably applies tension to the steel sheet, and the effect of reducing iron loss is excellent.
[0135] 《Other ingredients》
[0136] From the viewpoint of improving the heat resistance of the coating, the coating liquid may further contain inorganic mineral particles such as SiO2 (except for the above-mentioned silicon dioxide S), TiO2, and Al2O3.
[0137] In order to achieve a better heat resistance effect, the molar ratio of the content of inorganic mineral particles to the content of silicon dioxide S in terms of SiO2 in the coating liquid (inorganic mineral particles / S) is preferably 0.001 or more. On the other hand, from the viewpoint of improving the lamination factor, the molar ratio is preferably 0.050 or less.
[0138] From the viewpoint of improving the heat resistance of the coating, the coating liquid may further contain a borate.
[0139] In order to achieve a better heat resistance effect, the molar ratio of the content of borate calculated as B2O3 to the content of silicon dioxide S calculated as SiO2 in the coating liquid (borate / S) is preferably 0.002 or more. On the other hand, from the viewpoint of suppressing cracks in the coating and improving corrosion resistance, the molar ratio is preferably 0.070 or less.
[0140] <Coating>
[0141] The coating liquid is applied to the surface of the steel plate (when a forsterite film is formed, the surface of the forsterite film). The coating method is not particularly limited, and a conventionally known method can be used.
[0142] After applying the coating liquid to the steel sheet, drying may be performed before baking.
[0143] The drying temperature is preferably 150° C. or higher, and more preferably 200° C. or higher. On the other hand, it is preferably 500° C. or lower, and more preferably 400° C. or lower.
[0144] The drying time (retention time at 150° C. or higher) is preferably 5 seconds or longer, more preferably 10 seconds or longer. On the other hand, it is preferably 120 seconds or shorter, more preferably 100 seconds or shorter.
[0145] <Baking>
[0146] The baking also serves as planarization annealing. The baking atmosphere is not particularly limited, and for example, a non-oxidizing atmosphere such as a nitrogen atmosphere, an oxidizing atmosphere containing water vapor, a reducing atmosphere such as an atmosphere containing hydrogen, or a mixed atmosphere thereof can be used.
[0147] The baking temperature is 700° C. or higher, preferably 720° C. or higher. In this temperature range, sufficient film formation is possible, so the obtained coating has excellent corrosion resistance and sufficient tension is applied to the steel sheet.
[0148] On the other hand, if the baking temperature is too high, the steel sheet may be subjected to creep deformation due to heat, and iron loss may increase. Therefore, from the viewpoint of reducing iron loss, the baking temperature is preferably 900° C. or less, and more preferably 880° C. or less.
[0149] The baking time is not particularly limited, and is, for example, 5 seconds or longer, and preferably 10 seconds or longer.
[0150] However, when the baking time is too long, there is still a situation where the steel sheet undergoes creep deformation and the iron loss increases. Therefore, from the viewpoint of reducing the iron loss, the baking time is preferably 120 seconds or less, more preferably 90 seconds or less, and further preferably 60 seconds or less.
[0151] <Cooling>
[0152] The baked steel sheet is cooled from the baking temperature to, for example, room temperature while being conveyed by conveyor rollers.
[0153] The baking temperature is 700° C. or higher, and therefore, the baked steel sheet is cooled to at least 600° C. or lower in the process of being cooled to room temperature.
[0154] 《Forward Slip Rate r》
[0155] The forward slip ratio r (unit: %) is the percentage of the absolute value of the difference between the conveying speed X of the steel plate and the peripheral speed Y of the conveying roller (=radius×angular speed) relative to the peripheral speed Y of the conveying roller, and is expressed by the following formula.
[0156] r={|XY| / Y}×100
[0157] It can be said that the greater the forward slip rate r, the greater the friction between the steel plate and the conveying roller.
[0158] In the conveying area (hereinafter referred to as "cooling conveying area" for convenience) where the steel sheet is cooled to below 600°C after baking, the components in the coating liquid (coating components) solidify to form a coating. At this time, if the forward slip ratio r is too large, the formed coating is scratched to form convex parts and is prone to roughening. That is, the interlayer current value after the friction test is prone to increase.
[0159] Therefore, the forward slip ratio r of the cooling conveying area is 1.7% or less. As a result, the formed coating is not excessively roughened, and the interlayer current value after the friction test is reduced.
[0160] In order to achieve a more excellent effect, the forward slip ratio r of the cooling conveying region is preferably 1.4% or less, more preferably 1.0% or less, and further preferably 0.6% or less.
[0161] The lower limit of the forward slip ratio r in the cooling conveying region is not particularly limited, but if it is too small, the steel sheet is likely to meander or form steps during coiling, which may be a manufacturing problem.
[0162] Therefore, from the viewpoint of suppressing meandering of the steel sheet and improving productivity, the forward slip ratio r in the cooling conveying region is preferably greater than 0.1%, more preferably 0.12% or more, and even more preferably 0.2% or more.
[0163] Example
[0164] Hereinafter, the present invention will be described in detail with reference to examples, but the present invention is not limited to the examples described below.
[0165] [Example A]
[0166] <Manufacturing of Grain-Oriented Electrical Steel Sheets>
[0167] According to the manufacturing method of the present invention described above, a coating is formed while conveying a steel sheet, thereby manufacturing a grain-oriented electrical steel sheet (including some comparative examples).
[0168] As the steel sheet to be coated, a grain-oriented silicon steel (magnetic flux density B8: 1.91 T, iron loss W 2 ) after final annealing was prepared. 17 / 50 :0.75W / kg).
[0169] On both surfaces of the prepared steel plate, the pressure should be 5g / m2 per side after drying. 2 A coating liquid containing colloidal silica (SiO2), calcium dihydrogen phosphate (Ca(H2PO4)2), phosphoric acid (H3PO4) and zirconium oxide sol (ZrO2) was applied in an amount of . The content of each component of the coating liquid was changed so that each molar ratio (M1 / S, M2 / S and P / S) was changed as shown in Table 2 below.
[0170] After coating, the steel was dried (250°C, 50 seconds), and then baked at 850°C, 10 seconds in a dry nitrogen atmosphere, which also served as a flattening annealing. The steel was then cooled to room temperature and wound into a coil. The forward slip rate r of the conveying zone (cooling conveying zone) cooled to 600°C or less was changed as shown in Table 2 below. In this way, a grain-oriented electrical steel sheet was obtained.
[0171] <Hardness, maximum peak height Sp and interlayer current value>
[0172] The hardness and maximum peak height Sp of the coating were measured for the obtained grain-oriented electrical steel sheet according to the above-mentioned method. The results are shown in Table 2 below.
[0173] Furthermore, the obtained grain-oriented electrical steel sheet was subjected to a friction test under the conditions of a surface pressure of 200 Pa, a friction speed of 0.10 m / sec, a reciprocating stroke of 50 mm, and a reciprocating number of 90 times, and the interlayer current value after the friction test was measured. The results are shown in Table 2 below.
[0174] <Insulation>
[0175] The obtained grain-oriented electromagnetic steel sheet is processed into an iron core to make a transformer.
[0176] Specifically, a transformer was produced based on the method described in paragraph 0019 of International Publication No. 2018 / 181831. The produced transformer was subjected to a withstand voltage test described in 9.9.1 to 9.9.4 of JIS C 4304:2013 to confirm the presence or absence of leakage current and partial discharge.
[0177] When the occurrence of leakage current and partial discharge was not confirmed in all the tests, "○" was recorded in the following Table 2, and when the leakage current or partial discharge was confirmed in any test, "×" was recorded in the following Table 2. If "○", it can be evaluated that the insulation (interlayer resistance) is excellent even when the grain-oriented electromagnetic steel sheet is used in an actual transformer.
[0178] <Iron loss W 17 / 50 >
[0179] The iron loss W of the obtained grain-oriented electrical steel sheet was measured in accordance with JIS C 2556:2015. 17 / 50 The results are shown in Table 2 below.
[0180] [Table 2]
[0181] Table 2
[0182]
[0183] <Summary of evaluation results>
[0184] 《Example A1 to Example A7》
[0185] Among Examples A1 to A7, in Example A1 where the molar ratio M1 / S was less than 0.15, the hardness of the coating exceeded 9.0 GPa, the interlayer current value after the friction test exceeded 0.10 A, and the insulation properties were insufficient.
[0186] In contrast, in Examples A2 to A7 where the molar ratio M1 / S was 0.15 or more, the hardness of the coating was 9.0 GPa or less, and the interlayer current value after the friction test was 0.10 A or less, indicating good insulation properties.
[0187] Among Examples A2 to A7, in Examples A2 to A6 where the molar ratio M1 / S was 0.35 or less, the hardness of the coating was 6.0 GPa or more, and the iron loss was smaller than that of Example A7 which did not satisfy this requirement.
[0188] "Example A8~Example A14"
[0189] In Examples A8 to A14, in Examples A13 and A14 where the molar ratio M2 / S exceeded 0.15, the maximum peak height Sp of the coating exceeded 6.0 μm, and the interlayer current value after the friction test exceeded 0.10 A, indicating insufficient insulation.
[0190] In contrast, in Examples A8 to A12 where the molar ratio M2 / S was 0.15 or less, the maximum peak height Sp of the coating was 6.0 μm or less, and the interlayer current value after the friction test was 0.10 A or less, indicating good insulation properties.
[0191] Among Examples A8 to A12, Examples A9 to A12 in which the molar ratio M2 / S was 0.02 or more had smaller iron losses than Example A8 which did not satisfy this requirement.
[0192] "Example A15~Example A21"
[0193] Among Examples A15 to A21, in Examples A15 and A16 in which the molar ratio P / S was less than 0.20, the hardness of the coating exceeded 9.0 GPa, and the interlayer current value after the friction test exceeded 0.10 A, indicating insufficient insulation properties.
[0194] In contrast, in Examples A17 to A21 in which the molar ratio P / S was 0.20 or more, the hardness of the coating was 9.0 GPa or less, and the interlayer current value after the friction test was 0.10 A or less, indicating good insulation properties.
[0195] Among Examples A17 to A21, Examples A17 to A19 having a molar ratio P / S of 0.40 or less had smaller iron losses than Examples A20 to A21 not satisfying this.
[0196] "Example A22~Example A28"
[0197] In Examples A22 to A28, in Examples A27 and A28 where the forward slip ratio r in the cooling conveying region exceeded 1.7%, the maximum peak height Sp of the coating exceeded 6.0 μm, and the interlayer current value after the friction test exceeded 0.10 A, indicating insufficient insulation.
[0198] In contrast, in Examples A23 to A26 in which the forward slip ratio r in the cooling conveying region was 1.7% or less, the maximum peak height Sp of the coating was 6.0 μm or less, and the interlayer current value after the friction test was 0.10 A or less, indicating good insulation properties.
[0199] In addition, in Example A22 in which the forward slip ratio r in the cooling conveying region was 0.1%, meandering occurred in the steel sheet, and therefore each evaluation was not performed ("-" is described in each column in the above Table 2).
[0200] "Example A29~Example A35"
[0201] In Examples A29 to A35, the forward slip ratio r in the cooling conveying region was changed from 0.6% to 2.2%, respectively, and the other points were the same as Examples A1 to A7.
[0202] In Examples A29 to A35 in which the forward slip ratio r in the cooling conveying region exceeded 1.7%, the maximum peak height Sp of the coating exceeded 6.0 μm, and the interlayer current value after the friction test exceeded 0.10 A, indicating insufficient insulation properties.
[0203] [Example B]
[0204] <Manufacturing of Grain-Oriented Electrical Steel Sheets>
[0205] According to the manufacturing method of the present invention described above, a coating is formed while conveying a steel sheet, thereby manufacturing a grain-oriented electrical steel sheet (including some comparative examples).
[0206] As a steel sheet to be coated, a steel sheet (grain-oriented electrical steel sheet, sheet thickness: 0.23 mm) produced by a conventional method and subjected to final annealing was prepared. After final annealing, unreacted annealing separator was removed and then pickling was performed with phosphoric acid.
[0207] On both surfaces of the prepared steel plate, the coating should be 10 g / m2 per side after drying. 2 A coating liquid having a composition shown in Table 3 below was applied in an amount of .
[0208] As the supply source of the metal element M1, zinc sulfate (ZnSO4), lithium nitrate (LiNO3), magnesium dihydrogen phosphate (Mg(H2PO4)2) and calcium dihydrogen phosphate (Ca(H2PO4)2) were used. When the coating liquid does not contain the metal element M1, "-" is recorded in the following Table 3.
[0209] As the supply source of the metal element M2, titanium dioxide sol (TiO2), chromic anhydride (CrO3) and aluminum dihydrogen phosphate (Al(H2PO4)3) were used. When the coating liquid does not contain the metal element M2, "-" is recorded in the following Table 3.
[0210] Furthermore, the coating liquid preferably contains phosphoric acid (H3PO4) in addition to colloidal silica (SiO2).
[0211] After coating, the steel sheet was dried (300°C, 50 seconds), and then baked at 800°C, 10 seconds in a dry nitrogen atmosphere, which also served as a flattening annealing, and then cooled to room temperature. The forward slip ratio r in the conveying zone (cooling conveying zone) cooled to 600°C or less was set to 1.2%. In this way, a grain-oriented electrical steel sheet was obtained.
[0212] <Hardness, maximum peak height Sp and interlayer current value>
[0213] The hardness and maximum peak height Sp of the coating film were measured for the obtained grain-oriented electrical steel sheet in the same manner as in Example A, and the interlaminar current value after the friction test was also measured. The results are shown in Table 3 below.
[0214] <Insulation and iron loss W 17 / 50 >
[0215] The obtained grain-oriented electrical steel sheet was evaluated for insulation properties in the same manner as in Example A, and the iron loss W was measured. 17 / 50 The results are shown in Table 3 below.
[0216] [Table 3]
[0217] Table 3
[0218]
[0219] <Summary of evaluation results>
[0220] "Example B1~Example B5"
[0221] Among Examples B1 to B5, in Example B1 where the molar ratio M1 / S was less than 0.15, the hardness of the coating exceeded 9.0 GPa, the interlayer current value after the friction test exceeded 0.10 A, and the insulation properties were insufficient.
[0222] In contrast, in Examples B2 to B5 where the molar ratio M1 / S was 0.15 or more, the hardness of the coating was 9.0 GPa or less, and the interlayer current value after the friction test was 0.10 A or less, indicating good insulation properties.
[0223] "Example B6~Example B10"
[0224] In Examples B6 to B10 in which the molar ratio M2 / S was 0.15 or less, the maximum peak height Sp of the coating was 6.0 μm or less, and the interlayer current value after the friction test was 0.10 A or less, indicating good insulation properties.
[0225] Among them, Examples B7 to B10 in which the molar ratio M2 / S was 0.02 or more had smaller iron losses than Example B6 which did not satisfy this requirement.
[0226] [Example C]
[0227] <Manufacturing of Grain-Oriented Electrical Steel Sheets>
[0228] According to the manufacturing method of the present invention described above, a coating is formed while conveying a steel sheet, thereby manufacturing a grain-oriented electrical steel sheet (including some comparative examples).
[0229] As steel sheets to be coated, various steel sheets (oriented electromagnetic steel sheets) after final annealing were prepared. It should be noted that after final annealing, pickling was performed using phosphoric acid after removing the unreacted annealing separator. The composition of each steel sheet is shown in Table 4 below. In Table 4 below, "Tr" indicates that each component is below the quantitative limit.
[0230] On both surfaces of the prepared steel plate, the pressure should be 15 g / m2 per side after drying. 2 The same coating liquid as in Example A1 or Example A5 (see Table 2) was applied in an amount of.
[0231] Thereafter, drying, baking and cooling were performed under the same conditions as in Example A. The forward slip ratio r in the cooling conveying zone was set to 0.6%. In this way, a grain-oriented electrical steel sheet was obtained.
[0232] <Hardness, maximum peak height Sp and interlayer current value>
[0233] The hardness and maximum peak height Sp of the coating film were measured for the obtained grain-oriented electrical steel sheet in the same manner as in Example A, and the interlaminar current value after the friction test was further measured. The results are shown in Table 4 below.
[0234] <Insulation and iron loss W 17 / 50 >
[0235] The obtained grain-oriented electrical steel sheet was evaluated for insulation properties in the same manner as in Example A, and the iron loss W was measured. 17 / 50 The results are shown in Table 4 below.
[0236]
[0237] <Summary of evaluation results>
[0238] "Example C1 ~ Example C12"
[0239] In Examples C1 to C12, in Examples C11 and C12 where the molar ratio M1 / S was less than 0.15, the hardness of the coating exceeded 9.0 GPa, the interlayer current value after the friction test exceeded 0.10 A, and the insulation properties were insufficient.
[0240] In contrast, in Examples C1 to C10 where the molar ratio M1 / S was 0.15 or more, the hardness of the coating was 9.0 GPa or less, and the interlayer current value after the friction test was 0.10 A or less, indicating good insulation properties.
Claims
1. A grain-oriented electrical steel sheet comprising a steel sheet and coatings disposed on both surfaces of the steel sheet, The interlayer current value after the friction test is less than 0.10A. The hardness of the coating is 9.0 GPa or less. The surface roughness of the coating is 6.0 μm or less in terms of maximum peak height Sp. in, The friction test was conducted by stacking two of the grain-oriented electrical steel sheets and reciprocating 90 times under the conditions of a surface pressure of 200 Pa, a friction speed of 0.10 m / sec, and a reciprocating stroke of 50 mm.
2. The grain-oriented electrical steel sheet according to claim 1, wherein: The steel plate has a steel composition containing, by mass%, 2.0 to 4.0% Si and 0.03 to 0.25% Mn, with the balance being Fe and inevitable impurities.
3. The grain-oriented electrical steel sheet according to claim 2, wherein: The steel composition further contains, in mass %, at least one selected from the group consisting of Ni: 1.50% or less, Cr: 0.50% or less, Cu: 0.50% or less, P: 0.100% or less, Sb: 0.500% or less, Sn: 0.500% or less, Bi: 0.100% or less, Mo: 0.100% or less, Nb: 0.0100% or less, V: 0.010% or less, Ti: 0.010% or less, and Ta: 0.010% or less.
4. A method for manufacturing a grain-oriented electromagnetic steel sheet, comprising: applying a coating liquid to a conveyed steel sheet, baking at a temperature of 700° C. or higher, and cooling the steel sheet to form a coating on both surfaces of the steel sheet, wherein the interlayer current value of the grain-oriented electromagnetic steel sheet after a friction test is 0.10 A or less, wherein: The forward slip ratio r of the conveying area where the steel plate is cooled to below 600°C is below 1.7%, In the coating liquid, a molar ratio M1 / S1 of the content of the metal element M1 to the content of the silicon dioxide S1 calculated as SiO2 is greater than 0.15, a molar ratio M2 / S1 of the content of the metal element M2 to the content of the silicon dioxide S1 calculated as SiO2 is less than 0.15, and a molar ratio P1 / S1 of the content of the phosphoric acid component P1 calculated as P2O5 to the content of the silicon dioxide S1 calculated as SiO2 is greater than 0.20, in, The metal element M1 is at least one selected from the group consisting of Zn, Li, Mg and Ca, and the metal element M2 is at least one selected from the group consisting of Zr, Ti, Cr and Al. The friction test is conducted by stacking two grain-oriented electrical steel sheets and reciprocating 90 times under the conditions of a surface pressure of 200 Pa, a friction speed of 0.10 m / sec, and a reciprocating stroke of 50 mm. The forward slip rate r is the percentage of the absolute value of the difference between the conveying speed X of the steel plate and the peripheral speed Y of the conveying roller relative to the peripheral speed Y of the conveying roller, and is expressed by the following formula: r={|XY| / Y}×100.
5. A method for evaluating a grain-oriented electrical steel sheet, the method comprising evaluating a grain-oriented electrical steel sheet comprising a steel sheet and films disposed on both surfaces of the steel sheet, wherein: A friction test is performed to obtain an interlayer current value of the grain-oriented electromagnetic steel sheet after the friction test, and the insulation quality of the grain-oriented electromagnetic steel sheet is determined based on the obtained interlayer current value, and when the interlayer current value is 0.10 A or less, the insulation quality of the grain-oriented electromagnetic steel sheet is determined to be good. The friction test is performed by overlapping two grain-oriented electrical steel sheets and reciprocating 60 to 120 times under the conditions of a surface pressure of 150 to 250 Pa, a friction speed of 0.05 to 0.15 m / sec, and a reciprocating stroke of 30 to 70 mm.
Citation Information
Patent Citations
JP1978028375B2
JP1981052117B2
Transformer iron core
WO2018181831A1
Oriented electromagnetic steel plate
CN110832112A